ANALISIS EFEKTIVITAS MESIN CNC PUNCH & DRILLING SCM MODEL TPPRD130 PADA HALL 3 PT OMETRACO ARYA SAMANTA MENGGUNAKAN METODE TOTAL EFFECTIVE EQUIPMENT PERFORMANCE (TEEP) - Hisyam Rafly Syahputra; Farizi Rachman; Rizal Indrawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2024)
PT. Ometraco Arya Samanta, a construction services company specializing in civil and steel construction, experienced problems with the CNC Punch machine in the Hall 3 fabrication area . The P 15 type FICEP CNC Punch machine stopped operating due to software and sensor damage. As a result, most of the workload is shifted to the Model TPPRD130 SCM CNC Punch & Drilling machine. These machines experience deterioration in performance and component damage due to increased workloads. To overcome this problem, the researcher calculates the availability rate, performance rate, and quality rate values to calculate the Overall Equipment Effectiveness (OEE), which is then multiplied by the utilization of the machine to get the Total Effective Equipment Performance (TEEP) value. The results of the analysis show that the TEEP of the SCM Model TPPRD130 CNC Punch & Drilling machine for the period of December 4, 2023 — December 16, 2023 is 16.56%. The magnitude of Total Effective Equipment Performance (TEEP) is still not in accordance with the TEEP global standard value of 80%. there is still a very wide difference of 63.44% between the global standard value of TEEP and the value of TEEP in the Company